Behavioral Intentions of Generation Z and Millennial Users of Telemedicine: A UTAUT 2 Analysis from the Halodoc User Perspective - Hidayah, Nur Aeni; Utami, Meinarini Catur; Rizki, Irfan Nur (Journal of Information System and Informatics, 2024)
The rapid development of telemedicine has significantly transformed health services, leveraging technological sophistication to enhance medical consultations and treatments. Halodoc, a leading telemedicine application, has positively impacted the health sector. However, user reviews on the Google Play Store indicate issues that may affect user satisfaction and behavioral intention. Despite Millennials and Generation Z being major digital platform users, Generation X reports the highest satisfaction with telemedicine services. This study aims to validate the factors influencing and interrelating user satisfaction and behavioral intention in using the Halodoc application. Employing a quantitative approach with PLS-SEM data analysis, the study integrates the UTAUT 2 model with the Delone & McLean model. The results reveal that out of eight hypotheses, seven are supported, with Effort Expectancy on User Satisfaction being the only rejected hypothesis. The findings highlight that User Satisfaction significantly influences Behavioral Intention, underscoring the importance of enhancing user experience to improve telemedicine adoption.